Smoking and life expectancy among HIV-infected individuals on antiretroviral therapy in Europe and North America - Helleberg, Marie; May, Margaret T; Ingle, Suzanne M; Dabis, Francois; Reiss, Peter; Fätkenheuer, Gerd; Costagliola, Dominique; d'Arminio, Antonella; Cavassini, Matthias; Smith, Colette; Justice, Amy C; Gill, John; et al. (AIDS (London), 2015)
Cardiovascular disease and non-AIDS malignancies have become major causes of death among HIV-infected individuals. The relative impact of lifestyle and HIV-related factors are debated. We estimated associations of smoking with mortality more than 1 year after antiretroviral therapy (ART) initiation among HIV-infected individuals enrolled in European and North American cohorts. IDUs were excluded. Causes of death were assigned using standardized procedures. We used abridged life tables to estimate life expectancies. Life-years lost to HIV were estimated by comparison with the French background population. Among 17,995 HIV-infected individuals followed for 79,760 person-years, the proportion of smokers was 60%. The mortality rate ratio (MRR) comparing smokers with nonsmokers was 1.94 [95% confidence interval (95% CI) 1.56-2.41]. The MRRs comparing current and previous smokers with never smokers were 1.70 (95% CI 1.23-2.34) and 0.92 (95% CI 0.64-1.34), respectively. Smokers had substantially higher mortality from cardiovascular disease, non-AIDS malignancies than nonsmokers [MRR 6.28 (95% CI 2.19-18.0) and 3.31 (95% CI 1.80-5.45), respectively]. [corrected]. Among 35-year-old HIV-infected men, the loss of life-years associated with smoking and HIV was 7.9 (95% CI 7.1-8.7) and 5.9 (95% CI 4.9-6.9), respectively. The life expectancy of virally suppressed, never-smokers was 43.5 years (95% CI 41.7-45.3), compared with 44.4 years among 35-year-old men in the background population. Excess MRRs/1000 person-years associated with smoking increased from 0.6 (95% CI -1.3 to 2.6) at age 35 to 43.6 (95% CI 37.9-49.3) at age at least 65 years. Well treated HIV-infected individuals may lose more life years through smoking than through HIV. Excess mortality associated with smoking increases markedly with age. Therefore, increases in smoking-related mortality can be expected as the treated HIV-infected population ages. Interventions for smoking cessation should be prioritized.